Perancangan Sistem Informasi Koperasi Bahagia Bersama (KBB) Berbasis Web pada Mahkamah Syar'iyah Kota Banda Aceh Kelas I-A - Fahlevi, Muhammad Reza; Idwan, Harry (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2025)
The cooperative at the Mahkamah Syar'iyah Banda Aceh faces several challenges, one of which is the limited number of cooperative management personnel involved in developing cooperative business activities. The author identifies two main issues. First, from the perspective of cooperative members, there is difficulty in determining the amount of savings or loans, as the cooperative managers are not always present at the location. Second, from the perspective of the management, the bookkeeping process is still conducted manually. The purpose of this design is to provide easy access to information for members, such as the cooperative profile, savings balance, outstanding loans, and remaining installments. This system also aims to increase the trust of members towards the officers and to facilitate cooperative officers in generating more accurate and efficient reports. From the management side, the system provides access to an admin login page, home, master savings type, master member, savings transaction, loans, repayments, and savings reports. From the member's side, the system allows them to view the amount of their savings and loans. The web-based cooperative information system design at the Mahkamah Syariyah Banda Aceh utilizes fast web technologies for data processing, making reporting more efficient. This system is designed to facilitate data entry, data processing, and data storage, allowing easy access for various purposes such as data retrieval and reporting. The advantages of the Bahagia Bersama Cooperative program include its ability to generate savings reports, loan reports, and member lists.